A Novel Synthesis of Quinazolines by Cyclization of 1‐(2‐Isocyanophenyl)alkylideneamines Generated by the Treatment of 2‐(1‐Azidoalkyl)phenyl Isocyanides with NaH. Issue 6 (June 2014) - Ezaki, Kosuke; Kobayashi, Kazuhiro
Abstract A new and efficient method for the synthesis of quinazolines has been developed. Thus, N‐[2‐(1‐azidoalkyl)phenyl]formamides 1 are dehydrated with POCl3 to give the corresponding 2‐(1‐azidoalkyl)phenyl isocyanides 2, which are then treated with NaH in DMF at 0° to give quinazolines 6 in satisfactory yields via cyclization of 1‐(2‐isocyanophenyl)alkylideneamine intermediates 4. This methodology can be applied to the synthesis of the 7‐azaanalogs of quinazolines, i.e., pyrido[3, 4‐d]pyrimidines 9.